The Analysis of English Final Test at the First Semester of Indonesian Language and Literature Education of IPTS in 2021/2022 Academic Year - Devi Arissa (JURNAL LINER (Language Intelligence and Educational Research), 2022)
Abstract:The purpose of this research is to know the quality of English final test based on difficulty index, discrimination power, concurrent validity, and item validity. This research used descriptive quantitative method. The population of this research all of the first semester students of Indonesian Language and Literature Education of IPTS in 2021/2022 academic year which consist of 38 students and they were taken by using total sampling technique. Based on difficulty index shows the test is medium category which includes 8 items are difficult category (40%), 12 items are medium category (60%), and 0 item is easy category (0%). Furthermore on descrimination power the test is satisfactory category which includes 2 items are very poor category (10%), 5 items are poor category (25%), 8 items are satisfactory category (40%), 5 items are good category (25%), and 0 item is excellent category (0%). Then, for the concurrent validity the test is invalid because rxy is lower than rt (0,116 < 0,320). Meanwhile for the item validity there are 13 items are valid category (65%) and 7 items are invalid category (35%).Key words: English Final Test, Difficulty Index, Discrimination Power, Concurrent Validity, Item Validity Abstrak: Tujuan penelitian ini adalah untuk mengetahui kualitas soa lujian akhir Bahasa Inggirs berdasarkan tingkat kesukaran, daya pembeda, validitas bandingan, dan validitas buti rsoal. Penelitian ini menggunakan metode deskriptif kuantitatif. Populasi penelitian ini adalah seluruh mahasiswa semester satu pendidikan Bahasa dan Sastra Indonesia di IPTS tahun ajaran 2021/2022 yang terdiri dari 38 mahasiswa dan diambil menggunakan teknik total sampling. Berdasarkan tingkat kesukaran menunjukkan bahwa tes termasuk kategori mudah yang mencakup 8 soal kategori sulit (40%), 12 soal kategori sedang (60%), dan 0 soal kategori mudah (0%). Selanjutnya, pada daya pembeda menunjukkan bahwa tes termasuk kategori cukup yang mencakup 2 soal kategori sangat buruk (10%), 5 soal kategori buruk (25%), 8 soal kategori cukup (40%), 5 soal kategori baik (25%), dan 0 soal kategori baik sekali (0%). Kemudian, untuk validitas bandingan tes tersebut tidak valid karena rxy lebih rendah daripada rt (0,116 < 0,320). Sementara untuk validitas butir soal terdapat 13 soal kategori valid (65%) dan 7 soal kategori tidak valid (35%).Kata Kunci: Soal Ujian Akhir Bahasa Inggris, Tingkat Kesukaran, Daya Pembeda, Validitas Bandingan, Validitas Butir Soal.